2001
DOI: 10.3168/jds.s0022-0302(01)74669-3
|View full text |Cite
|
Sign up to set email alerts
|

Cracked Dry or Finely Ground High Moisture Shelled Corn as a Supplement for Grazing Cows

Abstract: Feeding shelled corn as the primary supplement in cracked dry form or ground high moisture form to grazing cows was studied in an experiment using 32 cows in late lactation. Each of the two forms of corn accounted for 74.7% of the concentrate supplement, which was fed at 9 kg/d (DM). The experiment was 13 wk, during which cows grazed permanent native pasture containing mostly grasses and some clover. Milk yield was 2.4 kg/d higher for cows fed ground high moisture shelled corn than for those fed dry cracked sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Therefore, one of the challenges of using pasture is maximizing ruminal N capture. This is often achieved by offering a compound feed consisting mainly of grain, with the type and processing method of grains having different effects (Reis and Combs, 2000;Wu et al, 2001;Mulligan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the challenges of using pasture is maximizing ruminal N capture. This is often achieved by offering a compound feed consisting mainly of grain, with the type and processing method of grains having different effects (Reis and Combs, 2000;Wu et al, 2001;Mulligan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a study with dairy cows, Knowlton et al (1998) and Alvarez et al (2001) reported that milk production was not influenced by HMCS inclusion in diets when compared with DGC. However, Wu et al (2001) obtained opposite results when HMCS inclusion was compared with DGC in diets for dairy cows and observed 2.4 kg/d more milk in animals fed diets with HMCS. San Emeterio et al (2000) compared different types of corn processing (HMCS and DGC) and particle size (fine or coarse) in diets for dairy cows and did not observe difference on milk production in animals fed once daily whereas when they were fed twice daily, milk production was higher in animals fed diets with HMCS.…”
Section: Resultsmentioning
confidence: 91%
“…Em apenas um trabalho a produção de leite foi maior para a fonte processada (Wu et al, 2001). A suplementação com grãos processados não afetou a gordura do leite em sete dos oito estudos sumarizados (Bargo et al, 1998;Pieroni et al, 1999;Reis e Combs, 2000;Soriano et al, 2000;Alvarez et al, 2001;Delahoy et al, 2003;Reis et al, 2001); Somente Wu et al (2001) relataram redução no conteúdo de gordura. Apenas dois de oito estudos (Alvarez et al, 2001;Wu et al, 2001) (Stern & Ziemer, 1993).…”
Section: Premissas Para Suplementação Com Concentradounclassified
“…A suplementação com grãos processados não afetou a gordura do leite em sete dos oito estudos sumarizados (Bargo et al, 1998;Pieroni et al, 1999;Reis e Combs, 2000;Soriano et al, 2000;Alvarez et al, 2001;Delahoy et al, 2003;Reis et al, 2001); Somente Wu et al (2001) relataram redução no conteúdo de gordura. Apenas dois de oito estudos (Alvarez et al, 2001;Wu et al, 2001) (Stern & Ziemer, 1993). Comparada com o milho, a polpa de citrus peletizada é um material com teor de amido baixo (Deaville et al, 1994), porém, apresenta características sob o aspecto de fermentação ruminal que a colocam como produto intermediário entre volumosos e concentrados (Fegeros et al, 1995).…”
Section: Premissas Para Suplementação Com Concentradounclassified